Esthetics of Music - Dahlhaus, Carl 1928-1989; Austin, William W. (Cambridge Cambridge University Press, 1982)
This book is an introduction to the esthetics of music. Aesthetics, which were of prime importance in thinking about music in the nineteenth century, are today sometimes suspected of being idle speculation. Yet judgments about music and every sort of musical activity are based on aesthetic presuppositions. Carl Dahlhaus gives an account of developments in the aesthetics of music from the mid-eighteenth century onwards. He combines a historical and systematic approach. Central themes in music are grouped together to illustrate both the historical course of events and a systematic unity of the essential elements in the aesthetics of music. For this edition, the late Carl Dahlhaus provided an annotated bibliography. William Austin has added books for the English-speaking reader, and has also supplied notes to the text to help the student.